The ADHD deficit in school performance across sex and parental education: A prospective sibling‐comparison register study of 344,152 Norwegian adolescents - Hans Fredrik Sunde; Thomas H. Kleppestø; Kristin Gustavson; Magnus Nordmo; Bjørn‐Atle Reme; Fartein Ask Torvik (Wiley, 2022)
Abstract Background Attention‐Deficit Hyperactivity Disorder (ADHD) is associated with impaired school performance, but the impact of ADHD may vary across sex, family background, and school subjects. By using prospective population‐wide register data, we describe impairment in academic performance related to ADHD across different school subjects and investigate how this impairment differ across sex and parental education. Methods We examined grades and Grade Point Averages (GPA) at age ∼16 among 344,152 Norwegian children born between 1997 and 2002. We linked grades with diagnoses from publicly funded general practitioners and with demographic information. Associations between ADHD diagnosed between age 10 and 16 and school performance were estimated with linear models, including sibling‐models which control for unobserved variables shared within families. Results Children with ADHD (4.0%) had −1.11 standard deviations lower GPAs compared to children without ADHD. This difference remained substantial after adjusting for demographic factors (−0.87), comorbid mental disorders (−0.82), early school performance (−0.54), and when comparing full siblings (−0.60). The relative ADHD deficit was 22% larger for girls than for boys and 39% larger for children with highly educated parents than for children of parents without completed high school, but the absolute deficit was smaller. Conclusion The ADHD deficit in school performance was large and not easily attributable to other factors. Because the ADHD deficit was large in all school subjects, interventions should ideally address factors that affect school performance broadly, although targeting theoretical subjects specifically may be most effective given limited resources.